Identifying gender issues to help students understand Malaysian fiction - MALA by K. S Maniam - Sapari, Karim (Universiti Malaysia Sarawak, (UNIMAS), 2005)
This study aims to find out the extent of how much the identifying gender issues help students to understand the short story. The sample was students of Form Four classes of S.M.K Lake, Bau. It is intended to highlight some of the important aspects that identifying gender issues can contribute to help students in learning of literature and to find out whether the students can identify the gender issues in the text. For the purpose of this study, the researcher had selected a text entitled "Mala" by K. S. Maniam, which is not a prescribed text learnt in Form Four Syllabus. Three instruments had been designed for data collection which were observation, comprehension questions and students' journal. The instruments had been materialized through lesson plans which administrated in stages within four days. The analysis is done using the percentage formula and it is written descriptively. From the analysis of the findings it revealed that the students able to identify the gender issues in the text used and it proved that identifying gender issues by looking at character and characterization helps to increase students' understanding towards the literary text used.